2013
DOI: 10.1007/s00432-013-1382-8
|View full text |Cite
|
Sign up to set email alerts
|

Androgen receptor expression is a predictive marker in chemotherapy-treated patients with endocrine receptor-positive primary breast cancers

Abstract: We provide evidence that AR expression is associated with chemotherapy responsiveness in ER-positive patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 25 publications
0
19
0
1
Order By: Relevance
“…Preclinical data for er-negative/Ar-positive breast cancer suggest a poor prognosis, but the results of this review refute this. this finding may be explained by the association of Ar with low proliferative activity as measured by Ki67 expression (26).…”
Section: Discussionmentioning
confidence: 90%
“…Preclinical data for er-negative/Ar-positive breast cancer suggest a poor prognosis, but the results of this review refute this. this finding may be explained by the association of Ar with low proliferative activity as measured by Ki67 expression (26).…”
Section: Discussionmentioning
confidence: 90%
“…ERa-positive cancers are more likely to be AR positive compared with other types of breast cancer (Gonzalez-Angulo et al 2009, Peters et al 2009, Luo et al 2010, Micello et al 2010, Niemeier et al 2010, Park et al 2010, Loibl et al 2011, Yu et al 2011). In the majority of studies, AR expression in ERa-positive tumours has been associated with favourable characteristics such as improved relapse-free survival, overall survival, response to endocrine treatments and chemotherapy, older age at diagnosis, lower tumour grade, lower Ki67 positivity, smaller tumour size and less necrosis (Gonzalez-Angulo et al 2009, Peters et al 2009, Castellano et al 2010, Niemeier et al 2010, Park et al 2011, 2012, Honma et al 2013, Witzel et al 2013. AR expression was also associated with improved overall survival for women with ERa-positive breast cancers in both meta-analysis studies (Qu et al 2013, Vera-Badillo et al 2014.…”
Section: Era-positive Breast Cancermentioning
confidence: 98%
“…AR expression in ERa-negative breast cancer is correlated with a lower Nottingham grade and apocrine differentiation (Niemeier et al 2010). The association between AR and survival is not so clear in ERa-negative breast cancers as in ERa-positive breast cancers; studies have reported either no association (Gonzalez et al 2008, Peters et al 2009, Park et al 2011 or an association with improved survival (Agoff et al 2003, Luo et al 2010, Witzel et al 2013). In addition, one meta-analysis reported that AR is associated with improved overall survival in ERa-negative breast cancer (Qu et al 2013), while the other reported no association (Vera-Badillo et al 2014).…”
Section: Era-negative Breast Cancermentioning
confidence: 99%
“…In women with TNBC, decreased rates of pathologic complete response were observed after neoadjuvant anthracycline-based chemotherapy (10% in a new TNBC subtype called “luminal AR” [LAR] vs 52% in other TNBC subtypes) (Lehmann et al 2011; Masuda et al 2013). Conversely, there is evidence that AR expression is predictive of chemotherapy responsiveness in ER+ disease, with improved 5-year event-free survival in tumors with high AR mRNA expression (74% vs 57%, P =0.013) and shorter event-free survival when AR mRNA expression was low (odds ratio [OR] 2.86, 95% CI 1.29−6.35, P = 0.01), adjusted for HER2, Ki67, tumor size, age and tumor grade (Witzel et al 2013). …”
Section: Breast Cancermentioning
confidence: 99%